Analysis of Students Creative Thinking Skills in Solving Problems on Global Warming Material Using the Rasch Model - Nurlita, Andreny Dwi; Suwarma, Irma Rahma; Aminudin, Ahmad (Journal La Edusci, 2025)
This study aims to analyze students’ creative thinking skills in solving physics problems related to the topic of global warming using the Rasch Model approach. Creative thinking is an essential component of 21st century skills, encompassing four main indicators: fluency, flexibility, originality, and elaboration. The research utilized a descriptive qualitative design supported by quantitative analysis using the Rasch Model to assess the quality of test items and the distribution of students’ abilities. A total of 25 eleventh-grade students from a public high school in Lebak Regency, Banten, participated in the study. The sample was selected using cluster random sampling. The instrument used consisted of eight open-ended essay questions that were validated by experts and tested for internal consistency, yielding a high reliability coefficient (α = 0.86). The results indicated a wide variation in students’ creative thinking skills. Most students fell into the high (28%) and moderate (24%) categories. The fluency aspect showed the highest achievement level (72%), reflecting students’ ability to generate ideas, while flexibility (63.5%) showed the lowest, suggesting challenges in producing ideas from diverse perspectives. Rasch model analysis showed that most test items were categorized as easy and did not sufficiently challenge higher-ability students. Interview data supported these findings, showing that students frequently gave generic responses lacking originality and depth. These results indicate that current physics instruction has not fully fostered students’ creative potential. Therefore, it is crucial to implement contextual, open-ended, and real-world problem-solving-oriented learning strategies to better support the development of creative thinking in physics education.